2018
DOI: 10.1021/acs.inorgchem.7b02747
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated in Vitro Anticancer Activity of Rhenium(I) Tricarbonyl Complexes Bearing Water-Soluble Phosphines

Abstract: Fifteen water-soluble rhenium compounds of the general formula [Re(CO)(NN)(PR)], where NN is a diimine ligand and PR is 1,3,5-triaza-7-phosphaadamantane (PTA), tris(hydroxymethyl)phosphine (THP), or 1,4-diacetyl-1,3,7-triaza-5-phosphabicylco[3.3.1]nonane (DAPTA), were synthesized and characterized by multinuclear NMR spectroscopy, IR spectroscopy, and X-ray crystallography. The complexes bearing the THP and DAPTA ligands exhibit triplet-based luminescence in air-equilibrated aqueous solutions with quantum yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
117
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 162 publications
3
117
0
1
Order By: Relevance
“…General Comments: [(Neocuproine)Re(CO) 3 (Cl)] ( 2ReCl ), [(Neocuproine)Re(CO) 3 (NCMe)]OTf ( 2ReNCMe ) and [(Phenantroline)Re(CO) 3 (NCMe)]OTf were synthesized according to the literature protocols , . Other reagents and solvents were used as received.…”
Section: Methodsmentioning
confidence: 99%
“…General Comments: [(Neocuproine)Re(CO) 3 (Cl)] ( 2ReCl ), [(Neocuproine)Re(CO) 3 (NCMe)]OTf ( 2ReNCMe ) and [(Phenantroline)Re(CO) 3 (NCMe)]OTf were synthesized according to the literature protocols , . Other reagents and solvents were used as received.…”
Section: Methodsmentioning
confidence: 99%
“…[32] Scheme 4. It is important to point out that Re-THP and Re-DAPTA compounds display triplet-based luminescence in air-equilibrated aqueous solutions (Φ = from 3.4 to 11.5 %), photo substitute one CO ligand (365 nm light; Φ = from 1.1 to 5.5 %) and sensitize the formation of 1 O 2 (Φ = up 70 %).…”
Section: Complexes With Pta and Derivatives Different To Dmoptamentioning
confidence: 99%
“…[6][7][8][9][10][11] In this context,our group has been exploringthe anticancera ctivity of polypyridyl rhenium(I) tricarbonyl complexes. [12][13][14][15] Certain members of this class of compounds exhibit potent cytotoxic activity,w hich can be leveragedf or their use as anticancer agents. [16][17][18][19][20][21][22][23] Here, we describe our investigation of an ew rhenium(I) tricarbonyl complexb earing ac helating polypyridyl liganda nd an axial isonitrile ligand as ap otent anticancer agent.O ur efforts to understand the mechanismo f actiono ft his tricarbonyl rhenium isonitrile polypyridyl (TRIP) complex ( Figure 1) have revealed that it is an effective ER stress-inducing agent with significant antiproliferativeactivity.…”
mentioning
confidence: 99%